Linguistic Landscape and the Representation of European Union Power in Robert Menasse’s Novel Die Hauptstadt - Megawati, Sri; Triyono, Sulis; Mala, Nila Viayanti (Journal of Language and Literature Studies, 2026)
Linguistic landscape research has increasingly moved beyond the inventory of public signage toward the interpretation of how visible language, naming practices, and semiotic arrangements construct social and political meanings. However, literary texts remain underexplored as semiotic environments in which public space can be narrated, selected, and ideologically organized. This article examines how European Union (EU) power and legitimacy are represented through a narrated linguistic landscape in Robert Menasse’s novel Die Hauptstadt. Using a qualitative interpretive textual design, the study treats the novel as the primary data source and integrates linguistic landscape theory, multimodal social semiotics, and Critical Discourse Analysis (CDA). Data were collected through systematic close reading and keyword-assisted searching of the PDF text to identify excerpts containing Brussels/EU toponyms, institutional labels, bureaucratic discourse, written-display references, multilingual routines, and legitimacy-related terms. The excerpts were documented in an excerpt log, translated when necessary, coded in two cycles, and interpreted through Fairclough’s textual, discursive, and social dimensions. The findings show that the novel represents EU authority as a semiotic achievement produced through spatial anchoring, institutional naming, bureaucratic classification, multilingual routines, and image-management discourse. At the same time, this authority is destabilized by counter-semiotic disruption, street-level contestation, and moral-memory motifs. The study concludes that Die Hauptstadt constructs Brussels as a narrated semiotic landscape where EU power becomes visible, persuasive, and fragile because legitimacy depends on signs, discourse, and public interpretation. The article contributes to linguistic landscape scholarship by demonstrating how fiction can function as an analytical site for examining narrated public space and political authority.